2016
DOI: 10.1093/hmg/ddw185
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic lysosome reformation dysfunction in glucocerebrosidase deficient cells: relevance to Parkinson disease

Abstract: Glucocerebrosidase (GBA1) gene mutations increase the risk of Parkinson disease (PD). While the cellular mechanisms associating GBA1 mutations and PD are unknown, loss of the glucocerebrosidase enzyme (GCase) activity, inhibition of autophagy and increased α-synuclein levels have been implicated. Here we show that autophagy lysosomal reformation (ALR) is compromised in cells lacking functional GCase. ALR is a cellular process controlled by mTOR which regenerates functional lysosomes from autolysosomes formed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 51 publications
7
191
1
1
Order By: Relevance
“…Unexpectedly we found that p-MTOR and p-RPS6 protein levels were decreased in Gba L444P/WT mouse brains. While contrary to our observation of suppressed autophagy induction, these data are consistent with recent studies in GD and GBA-PD patient-derived fibroblasts [49] and Gba1 -deficient Drosophila models [50] in which the hypoactive MTOR was proposed to be responsible for impaired recycling of functional lysosomes from autolysosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly we found that p-MTOR and p-RPS6 protein levels were decreased in Gba L444P/WT mouse brains. While contrary to our observation of suppressed autophagy induction, these data are consistent with recent studies in GD and GBA-PD patient-derived fibroblasts [49] and Gba1 -deficient Drosophila models [50] in which the hypoactive MTOR was proposed to be responsible for impaired recycling of functional lysosomes from autolysosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, lysosomal reformation is compromised in GCase‐deficient fibroblasts and is accompanied by an increase in total and phosphorylated α‐syn, oligomer deposition, and enhanced α‐syn release. This indicates that accumulation of defective lysosomes contributes to impaired autophagy and α‐syn buildup . It has also been suggested that protein phosphatase 2A inactivation could represent the potential mechanism through which GCase deficiency inhibits autophagy and promotes α‐syn aggregation .…”
Section: Mechanisms Underlying the Cross Talk Between Gcase And α‐Synmentioning
confidence: 99%
“…Additionally they are cost-effective and free from the ethical concerns that accompany primary cell and stem cell use [21,22]. In the case of GBA-PD research, cell lines stably expressing alpha-synuclein can be transfected with siRNA to silence GBA expression and thus serve as a robust model of reduced Gcase activity in a PD setting [23].…”
Section: Models Of Gba-pdmentioning
confidence: 99%
“…Fibroblast lines may also be derived from GBA mutationcarrying mice. These models allow investigation of the cellular mechanisms by which altered GCase activity may affect patient susceptibility to PD and can serve as an inexpensive model for testing potential drug treatments [23,26]. These lines, however, are not neuronal, and do not express alpha-synuclein, which can limit the key research questions that can be answered using them.…”
Section: Models Of Gba-pdmentioning
confidence: 99%